2019
DOI: 10.3390/cancers11070998
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation Status in Circulating Tumor DNA from Patients with Metastatic Colorectal Cancer: Extended Mutation Analysis from the AGEO RASANC Study

Abstract: In patients with metastatic colorectal cancer (mCRC), RAS and BRAF mutations are currently determined by tumor sample analysis. Here, we report BRAF mutation status analysis in paired tumor tissue and plasma samples of mCRC patients included in the AGEO RASANC prospective cohort study. Four hundred and twenty-five patients were enrolled. Plasma samples were analyzed by next-generation sequencing (NGS). When no mutation was identified, we used two methylated specific biomarkers (digital droplet PCR) to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…To our knowledge, our prospective DECALIB study was the first to use ddPCR for CRC and AA detection [ 37 ]. Our study showed that ddPCR was sensitive and specific for the detection of advanced CRC, but not for in situ carcinomas or advanced adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our prospective DECALIB study was the first to use ddPCR for CRC and AA detection [ 37 ]. Our study showed that ddPCR was sensitive and specific for the detection of advanced CRC, but not for in situ carcinomas or advanced adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for liquid biopsy in guiding treatment and monitoring the disease is compelling and may soon be translated to clinical practice. In recent years, ctDNA has been shown to be a powerful tool in (1) assessing the adequacy of surgical tumor clearance and thereby the risk of recurrence (2) in selecting the most appropriate targeted therapy and (3) in following responses to systemic treatments [73,74]. The reappearance or increase in ctDNA, along with the emergence of new mutations, is associated with recurrence, progression and resistance to therapy.…”
Section: Liquid Biopsy: Ctdna and Tumor Mutation Burdenmentioning
confidence: 99%
“…Whereas a large number of studies have addressed mCRC [15][16][17][18][19][20][21][22][23] only a few have investigated the role of liquid biopsy in early, non-metastatic CRC patients at surgery, e.g. in conditions of extremely low tumor burden [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%